Modelos para predizer exigências energéticas para codornas de corte - Zancanela, Vittor (2012)
Three assays were carried out with the purpose of studying the energetic metabolism of meat quails, through the determination of energetic requirements for weight maintenance and gaining, and the efficiency of recovery and deposition of energy such as fat and protein, formulating and proposing prediction equations of requirements of metabolizable energy for meat quails. In the Assay 1, it has been used 80 meat quails with 35 day old, housed in metabolism cages and distributed on a completely randomized design (CRD) with 4 treatments (ad libitum intake, 70, 50 and 30% of ad libitum intake) and 5 replicates each. The feed was formulated to supply the nutritional requirements for birds of that age. The values of intake and excreted gioss energy were determined and considering the balance of nitrogen it has been verified, in fresh matter, the apparent metabolizable energy corrected by nitrogen balance (AMEn) of the feed. The average values of AMEn were: 2.951 Kcal/kg, 2.907 kcal/kg, 2.898 kcal/kg and 3.162 kcal/kg respectively for treatments of ad libitum intake, 70, 50 and 30% of the ad libitum intake. In the Assay II, it has been used 620 non-sexed meat quails, on 15 days of age, distributed on a completely randomized design (CRD), with four treatments and five replicates, totaling 20 experimental units, with 31 birds each. The treatments consisted on ad libitum intake, 70, 50 and 30% of ad libitum intake, being the food intake quantified daily. Slaughters were carried out on 15 and 35 days old, using the comparative slaughter tecbnique by factorial design. The retained body energy (REc), heat production (HP) and metabolizable energy intake (MEl), were quantified regarding the metabolic weight of the birds. Using regression analysis of these variables it has been obtained the demands values of metabolizable energy of maintenance (MEm = 157.61 kcal/kg°/75/day), net energy of maintenance (NEm = 74.17 kcal/kg°/75/day), and also the efficiency of energy use (k). The respective values for total efficiency of energy use (Kgp), efficiency of maintenance (Km) and efficiency for fat deposition (Kg) and crude protein (Kp) were 0.47, 0.47, 0.79, 0.32. In the Assay III, it has been used 550 and 500 birds, respectively for the experimental lst phase (1 to 14 days) and experimental 2nd phase (15 to 35 days). The experimental design was entirely randomized (CRD), with 10 experimental units (box) of 55 birds (1 st phase) and 50 birds (2nd phase). Each two experimental units was a repetition, totalizing five replicates, where the birds were fed with a feed formulated according with their requirements on each phase. The slaughters were performed weekly, and through the regression of energy content in the carcass by the body weight, it was determined the requirement of net energy for weight gain, which was divided by the ME efficiency uses of diet (Assay II) provided the requirement of metabolizable energy for gain weight (MEg). The obtained values of MEg for the lst and 2nd phase were, respectively: 2.91 and 4.5 kcal/g. Determined the values of MEm and MEG, it has been proposed the prediction equations of the energetic requirements for meat quails in the period from 1 to 14 and from 15 to 35 days of age respectively: MEl = 157.61W°75 + 2.91G and MEl = 157.61W°75 + 4.5G.